Avaliação experimental de nanolubrificante CuO/Óxido de Grafeno/POE em refrigerador de pequeno porte - Cavalcanti, Breno Câmara (2021)
Nanofluids consist of a two phase mixture of solid particles of nanometric dimensions dispersed in a base fluid. In the literature, different nanoparticles have been used to investigate the ability to improve lubricants' tribological and thermal properties, obtaining potentially interesting results. This work has as the main objective the synthesis of a hybrid nanolubricant from graphene oxide (OG) and copper (CuO) nanoparticles in the proportion of 1: 1 and concentrations of 0.05; 0.1 and 0.2% by weight dispersed in commercial polyol ester synthetic oil. The samples were homogenized in an ultrasonic bath, and their stability was verified by the sedimentation method. The nanolubricant dynamic viscosity was determined in a temperature range of 10 to 60°C. The tribological performance was evaluated using the High Frequency Reciprocating Rig (HFRR) ball on disc test at 50°C, obtaining values for the coefficient of friction (COF), lubricating film formation, and wear scar diameter (WSD) of the ball. Thermal conductivity (k) is measured by the transient hot wire method at 25°C. The temperatures, pressures, and electrical power of a refrigerator were monitored, and it compared the system operating with commercial lubricants and nanolubricants. The nanoparticle's addition a minimal variation in dynamic viscosity, verifying a trend of increase for higher nanoparticle concentrations. Also, it was observed a reduction of up to 24% in the WSD and 15% in COF and a slight increase of up to 2 % for thermal conductivity. It was found a reduction in electrical power consumed by the compressor operating with nanolubricant of up to 4.1% and an increase in COP of up to 4.7%.